LICHEN PLANOPILARIS – A CASE ASSOCIATED WITH AUTOIMMUNE DISEASES - Ramos, Luana Oliveira (2014)
Due to the development of large areas of permanent alopecia, patients with lichen planopilaris are more likely to evolve with psychosocial disorders and lower quality of life. Lichen planopilaris (LPP) is characterized by an autoimmune response against antigens of the hair follicle. It is known that can coexist with systemic autoimmune diseases, although this relationship is not well understood. Early recognition and prompt therapy are to protect the base of the hair follicle and fibrosis can stop the progression of hair loss. We present a therapy used with excellent results in a case of lichen planus pillar overlap that occurred in dermatomyositis and scleroderma.